# 5y 1 6x 4y 10

The solution for the system of equations is x=?1,y=?1. Explanation: ?6x+5y=1 ….equation (1) 6x+4y=?10 ….equation (2).Algebra Examples. Popular Problems · Algebra. Solve by Addition/Elimination -6x+5y=1 , 6x+4y=-10.Solve your math problems using our free math solver with step-by-step solutions. Our math solver supports basic math, pre-algebra, algebra, trigonometry, Find an answer to your question Solve the following system of equations using the elimination method. 6x  5y = 1 6x  4y = 10.solve by elimination -6x+5y=1 6x+4y=-10. Good Question (171). Answer. 5. (874 votes). Clear explanation (84). Detailed steps (66).

View this answer now! It’s completely free.

## -6x+5y=1 6x+4y=-10

7x + 2y = 6 – 14x – 4y = -12 16. x – 4y = 2 4x – 16y = 8. 2 3 + 2y = -7 NIKNIK 18.. in y 20. 2x – 3y = 7 – 4x + 6y – 14 19. 5x – 5y = 3 x – y = 12 + + 10. Click here to get an answer to your question ?? 1 2 1 1 1 SOLUTION 2 + 2y +1 20 – 4+1=2 4x – 2y + 2 = 1 +2y +1 + 3x  4y = -1….eqi 3x – Y+1 2- +3. Rozwi?zuj zadania matematyczne, korzystaj?c z naszej bezp?atnej aplikacji, która wy?wietla rozwi?zania krok po kroku. Obs?uguje ona zadania z podstaw. Asked by aviralsangal31.9spicertl | 1st Jun, 2020, 10:57: AM. Expert Answer: · This question is based on solving simultaneous equations. The working till. 11x=22y x=2y i: Otrzyman? warto?? wstawiamy za x do równania 16(2y)-27y=0 5y=0 i: Rozwi?zujemy równanie 1) dla zmiennej y 5y=0 y=0 i: W tej chwili mamy :

## – 2x – 9y = – 25 – 4x – 9y = – 23

-2x-9y=-25 -4x-9y=-23. 2. See answers.Simple and best practice solution for -2x-9y=-25-4x-9y=-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, Click here to get an answer to your question ?? How do you solve -2x-9y=-25 and -4x-9y=-23?-2x-9y= -25 …….1 -4x-9y =-23 …….2. Eliminate y multiply (1)by -1. Multiply (2) by 1 2x+9y= 25 -4x-9y= -23. Add the two equations -2x= 2Find step-by-step Algebra solutions and your answer to the following textbook question: -2x – 9y = -25 -4x – 9y = -23.

## 5) – 2x – 9y = – 25; – 4x – 9y = – 23

-2x-9y=-25 -4x-9y=-23. 2. See answers.Simple and best practice solution for -2x-9y=-25-4x-9y=-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, 5) 2x  9y=-25 -4x  9y=-23. 2. See answers.Simple and best practice solution for -2x-9y=-25-4x-9y=-23. Check how easy it is, to solve this system of equations and learn it for the future.Find step-by-step Algebra solutions and your answer to the following textbook question: -2x – 9y = -25 -4x – 9y = -23.

## 8x + y = ?16 ?3x + y = ?5

The equations have the same coefficients for the y y y-terms so subtract the two equations to eliminate y y y. Then solve for x x x: 8 x + y = ? 16. 5x=5. X=1. 5+y=9 y=4. Algebra 1B. 2). (1,4). 4). 8x+y=-16. -3x+y=-5. 3x-4=5. 11x=-11. 3x+6y=65. -30+44=-14. 4y=16 y=4. (-6,4). 6). | ?3x + 7y=?16-3.We have 8x+y equals to (-16/-3)*x + y equals -5. Working from what you actually wrote: y²+2y?(1÷y)+1 = y²+2y+1?(1/y) = (y+1)² – 1/y.Simple and best practice solution for -8x-y=163x-y=5. Check how easy it is, to solve this system of equations and learn it for the future.x=?1 y=?8. Explanation: Subtracting ?3x+y=?5 from the Equation 8x+y=?16. We get. 8x?(?3x)+y?y=?16+5. or. 8x+3x+0=?11. or. 11x=?11.